ANALYSIS OF THE INFLUENCE OF THE EXTERNAL NASAL DILATOR ON THE AREA OF THE NASAL CAVITY IN REST AND ON THE MAXIMUM CAPACITY IN THE ACTIVITIES THAT USE THE OXYGEN FROM THE AIR AND THE HEART RATE IN CYCLE ERGOMETER (Fiep Bulletin - online, 2015)
Introduction: Athletes and trainers believe that the external nasal dilator (DNE) is capable to develop the physical capacity during predominantly activities that use oxygen from the air. This is justified due to the anatomical factors and mechanical itself, once, this device can generate an increase in the area of the nasal cavity. Objectives: First phase: To verify quantitatively if there is some alteration in the nasal cavity with the use of the DNE and to construct a placebo of DNE (ENDP). Second phase: to analyze if the DNE exerts influence on the maximum capacity in the activities that use oxygen from the air  (VO2max) and the heart rate (HR). Methodology: First phase: 8 individuals, healthful, of the masculine sort with age between 20 and 32 years that had passed for four experimental situations: Control Group (GC), with DNE and two different PDNE (PDNE1 and PDNE2), analyzed through acoustic rhinometry. Second phase: 12 volunteers did a maximum, gradual exercise in cycle ergometer in three situations: use of the DNE, the PDNE and the GC. They answered a questionnaire, analyzed for the Qui-square test (p
Keywords: nasal cavity; maximum capacity in the activities that use oxygen from the air; heart rate.